Waponahki Intellectual Tradition of Weaving Educational Policy - Cardinal Sockbeson, Rebecca (Alberta Journal of Educational Research, 2010)
This article describes an articulation of a Waponahki intellectual tradition from the experience of a Waponahki woman attempting to position Indigenous knowledge systems in the academy. The author shows how the Waponahki intellectual tradition of weaving baskets can serve as a theoretical framework and foundation for understanding Waponahki policymaking and research. The article reports on a new law implemented in 2004 in the State of Maine that mandates the teaching of Waponahki history and culture in kindergarten through grade 12 and how teacher education programs are being developed to prepare teachers to comply with the legislation. The vision of policy direction resides in the minds of the policymaker and the community for which and with which he or she works. Like policy development, the blueprints of design for the basketry are constructed in the mind of the basketmaker; both work toward the future and continued survival of the Waponahki people. Policy development and basketmaking are more than writing texts or weaving strips of wood: both rely heavily on experience, connection to the people, and knowledge of who we are. Our basketry is intrinsic to our culture, rooted in our creation story; similarly, our policy development is critical to our decolonization and survival. The article calls for Indigenous peoples to revitalize, preserve, recognize, or even uncover their own Indigenous intellectual traditions with the vision of expanding knowledge systems.